Low Level of Haptoglobin in Lupus - Homa Timlin MD, MSc; Kirthi Machireddy; Michelle Petri MD, MPH (SAGE Publishing, 2017)
Haptoglobin levels are measured in systematic lupus erythematosus patients as part of the workup for anemia, with low levels indicating hemolysis. Haptoglobin is an acute phase protein. We present 2 lupus patients who were found to have low haptoglobin levels in the absence of other evidence of hemolysis.